Does math education in Poland teach creative thinking? - Biernacki, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
This work is a continuation of the article (Biernacki, Czesak 2013), which examined the most recent results (2012) of the Program for International Student Assessment. It turned out that Polish students have significantly improved their results in general subjects, but have great difficulties with creative thinking (the results are below the median). Analysis of the results of examinations in mathematics for students of the first year of two departments confirmed that students have great difficulty with problem solving. The author proposes to encourage students through the use of exercises and labs to take more time to solve tasks that require creative thinking, especially those relating to real-world problems of physics and economics
Didactics of Mathematics, 2014, Nr 11 (15), s. 5-12
Keywords: effectiveness of mathematics education